Secondary music teachers: a case study at a time of education reform in Wales. (1st January 2023) - Breeze, Thomas; Beauchamp, Gary; Bolton, Nicola; McInch, Alex
ABSTRACT: Current international trends in curriculum design tend to advocate an approach which defines broad 'competences' rather than disciplinary content or skills, encouraging the making of connections between subject disciplines. This article discusses the results of a survey of 75 secondary music teachers in Wales, a nation which is in the early stages of implementing a new curriculum framework. The survey sought to form an impression of the musical backgrounds and training of the teachers, their pedagogic beliefs about classroom music, and their attitudes towards the values embodied in their new national curriculum. The responses from music teachers suggested that the majority had been musically educated in the Western 'classical' tradition at university, but their beliefs about teaching music in the classroom indicated that they had moved beyond the conception of the subject embodied in their own higher education, to a more holistic, practical conception in which pupils learn by doing. While a significant body of literature suggests the existence of a gap between the musical values of classroom music teachers and those of their pupils, the teachers surveyed for this research indicated that they tend to prioritise the development of transferable creativity skills over the production of excellent musicians. .